Pengaruh Motivasi Kerja, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada PT Mitra Megah Bangunan Tulungagung) - Muhammad Edi Soleh; Budi Wahono; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstrak The company not only expects capable, competent and skilled human resources, but the most important thing in the performance of employees is to work hard and honestly. Employee performance can be seen as something that has great benefits, both for the benefit of the company and for employees. This study aims to examine and analyze the effect of work motivation, work discipline, and work environment on employee performance. The object of this research is PT Mitra Megah Bangunan Tulungagung. The population in this study were 100 employees. The sampling method is saturated sample, so the number of samples in this study is 100. The method of data analysis is through multiple linear regression analysis. The results showed that work motivation, work discipline, and work environment simultaneously had a significant effect on employee performance. Partially, work motivation and work discipline have a significant effect on employee performance, while the work environment has no significant effect on employee performance. Keyword: Employee Performance, Work Motivation, Work Discipline, Work Environment